2011
DOI: 10.1373/clinchem.2011.169714
|View full text |Cite
|
Sign up to set email alerts
|

Altered Profile of Seminal Plasma MicroRNAs in the Molecular Diagnosis of Male Infertility

Abstract: BACKGROUND:Although microRNAs (miRNAs) play essential roles in spermatogenesis, little is known about seminal plasma miRNAs in infertile men. We investigated the profile of seminal plasma miRNAs in infertile men to identify miRNAs that are altered in infertility; we then evaluated their diagnostic value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
178
1
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 235 publications
(197 citation statements)
references
References 37 publications
8
178
1
10
Order By: Relevance
“…Our data indicates that over 100 miRNAs can be found within human spermatozoa, a number much more in agreement with other studies in murine and porcine spermatozoa, and in humans comparing the seminal plasma miRNA profiles of normozoospermic men with those suffering from asthenozoospermia and azoospermia. 40,46,47 Of the 130 miRNAs identified here, 28 were significantly (p < 0.05, after BH correction) differentially expressed in smokers compared with non-smokers ( Table 2 and Fig. 4).…”
Section: Discussionmentioning
confidence: 87%
“…Our data indicates that over 100 miRNAs can be found within human spermatozoa, a number much more in agreement with other studies in murine and porcine spermatozoa, and in humans comparing the seminal plasma miRNA profiles of normozoospermic men with those suffering from asthenozoospermia and azoospermia. 40,46,47 Of the 130 miRNAs identified here, 28 were significantly (p < 0.05, after BH correction) differentially expressed in smokers compared with non-smokers ( Table 2 and Fig. 4).…”
Section: Discussionmentioning
confidence: 87%
“…Recent studies also reported a significant difference in the concentration of some specific miRNAs in seminal plasma of infertile men [198,199]. For instance, Wang et al, [199], observed that 7 special miRNAs (miR-34c-5p, miR-122, miR146b-5p, miR-181a, miR-374b, miR-509 -5p and miR-513a-5p) are markedly decreased in semen of azoospermia but increased in asthenozoospermia.…”
Section: Mirnas In Spermmentioning
confidence: 98%
“…For instance, Wang et al, [199], observed that 7 special miRNAs (miR-34c-5p, miR-122, miR146b-5p, miR-181a, miR-374b, miR-509 -5p and miR-513a-5p) are markedly decreased in semen of azoospermia but increased in asthenozoospermia. They revealed a strong relationship between the seminal plasma miRNAs and male infertility, suggesting that the seminal plasma concentrations of these miRNAs can accurately distinguish infertile patients from fertile controls.…”
Section: Mirnas In Spermmentioning
confidence: 99%
See 1 more Smart Citation
“…Such information will not only increase the number of novel biomarkers for molecular diagnostics in infertility, but may also indicate a molecular mechanism underlying the spermatogenetic processes that regulate and control fertility. The molecular basis of male fertility dysfunction is largely unknown; however, several studies have revealed the role of certain genes or miRNAs in the male reproductive system [23,24]. We observed lower expression levels of CIB1 in oligoasthenozoospermia and asthenozoospermia patients than in control fertility patients.…”
Section: Discussionmentioning
confidence: 52%